Hubungan Efikasi Diri, Lama Terdiagnosis, dan Dukungan Sosial dengan Perilaku Pengendalian Hipertensi pada Wanita Dewasa di Wilayah Kerja Puskesmas Montasik Kabupaten Aceh Besar - Depa Raihan; Farrah Fahdhienie; Riza Septiani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Hypertension or high blood pressure, is a dangerous condition that often occurs without symptoms and can affect people of all ages. This disease is influenced by lifestyle factors, treatment compliance, and self-confidence. This study aims to identify hypertension control behaviors among adult women in the working area of the Montasik Community Health Center, Aceh Besar Regency. The study employed a quantitative approach with a cross-sectional design and involved 90 respondents selected using accidental sampling. Data collection was conducted through interviews using a questionnaire from January 4 to 7, 2025. Data analysis was performed using SPSS with univariate and bivariate analyses. The results showed that 40% of respondents did not engage in hypertension management behaviors, 40% had low self-efficacy, 42.2% had a duration of hypertension of less than 1 year, and 52.2% received low social support. Bivariate analysis showed a significant association between self-efficacy (p=0.000), duration of hypertension (p=0.000), and social support (p=0.010) with hypertension control behavior. However, there was no significant association between educational level (p=0.230) and hypertension control behavior. By identifying the factors influencing hypertension control behavior, healthcare workers need to collaborate with community leaders and health workers to enhance public awareness regarding healthy lifestyles and hypertension control.